2008
DOI: 10.19030/ctms.v4i10.5572
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Employment And Physical Activity On Academic Performance

Abstract: Over the last twenty years, many contributions appeared on the relationship between working during school and academic performance using both quantitative and qualitative research methods. The obvious assumption is that a full time working student will show a lower academic performance relatively to a part time working student or a full time student. However, the empirical evidence doesnt seem to support this assumption because other variables affect the academic performance such as talent, motivation, ambitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The results demonstrated that students who used the recreation center more often each semester were more likely to have higher GPAs than those students who only visited the center on an irregular basis. These results reflect previous study findings that exercise (Andreopoulos et al, 2011;El Ansari & Stock, 2010;Field et al, 2001;Keating et al, 2013) and student involvement on campus (Bergen-Cico & Viscomi, 2012;Sparkman, Maulding, & Roberts, 2012) can positively affect academic performance; however, neither of these latter studies assessed use of the recreation center specifically.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results demonstrated that students who used the recreation center more often each semester were more likely to have higher GPAs than those students who only visited the center on an irregular basis. These results reflect previous study findings that exercise (Andreopoulos et al, 2011;El Ansari & Stock, 2010;Field et al, 2001;Keating et al, 2013) and student involvement on campus (Bergen-Cico & Viscomi, 2012;Sparkman, Maulding, & Roberts, 2012) can positively affect academic performance; however, neither of these latter studies assessed use of the recreation center specifically.…”
Section: Discussionsupporting
confidence: 86%
“…Research into the specific effect of recreation facilities use on academic performance of undergraduate college students may be unique to this study. Similar studies have been conducted to show the relationship between exercise and academic performance in high school students (Field et al, 2001), exercise in relation to cognitive function of various populations (Brisswalter et al, 2002;Chang, et al, 2013), university engagement (Bergen-Cico & Viscomi, 2012Sparkman et al, 2012), or general exercise in relation to academic success in university students (Andreopoulos et al, 2011;El Ansari & Stock, 2010;Franz & Feresu, 2013). This study also had a larger sample size than any of the comparative studies seen in the literature review.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This result does not support the findings of Klott (1998) that working long hours at a job during the school year often has a detrimental effect on academic performance. The empirical evidence in the study of Andreopoulos, Antoniou, Panayides, and Vassiliou (2008) did not support the assumption that a full time working student will show a lower academic performance relative to a part time working student or a full time student because other variables affect academic performance such as talent, motivation, ambition, and efficiency of study time. The relationship between frequency of exercise and GWA is significant.…”
Section: Resultsmentioning
confidence: 88%